A Matched Case-Control Study of Risk Factors for Breast Cancer Risk in Vietnam. (13th December 2016) - Nguyen, J.; Le, Q. H.; Duong, B. H.; Sun, P.; Pham, H. T.; Ta, V. T.; Kotsopoulos, J.; Narod, S. A.; Ginsburg, O.
Abstract : Background . Vietnam has a low age-standardized incidence of breast cancer, but the incidence is rising rapidly with economic development. We report data from a matched case-control study of risk factors for breast cancer in the largest cancer hospital in Vietnam. Methods . 492 incident breast cancer cases unselected for family history or age at diagnosis and 1306 control women age 25–75 were recruited from the National Cancer Hospital (BVK), Hanoi. Structured interviews were conducted and pathology data was centrally reported at the National Cancer Hospital of Vietnam, in Hanoi. Results . Our analysis included 294 matched pairs. Mean age at diagnosis was 46.7 years. Lower mean parity, older age at first parity, increasing weight and BMI at age 18, and increasing BMI at diagnosis were positively correlated with breast cancer cases compared to controls. Age at first menarche and duration of breastfeeding were not statistically different between cases and controls. Conclusions . In this study we demonstrate that breast cancer in Vietnam is associated with some but not all of the published risk factors from Western populations. Our data is consistent with other studies of breast cancer in Asian populations.